Transcriptome dataset of sago palm in peat soil - Yan, Wei Jie; Hasnain, Hussain; Chung, Hung Hui; Norzainizul, Julai @Julaihi; Rina, Tommy (Elsevier Inc., 2022)
Sago palm (Metroxylon sagu Rottb.) is an important agricultural starch-producing palm that contributes to Malaysia's economics, especially in the State of Sarawak, Malaysian Borneo. In this palm tree, the central part of the plant storage-starch. Under normal condition, sago palm develop its trunk after 4-5 years being planted. However, sago palms planted on deep-peat soil failed to develop their trunk even after 17 years of being planted. This phenomenon is known as ‘non-trunking’, which eliminates the economic value of the palms. Numerous research has been done to address the phenomenon, but the molecular mechanisms of sago palm responding toward the responsible stresses are still lacking. Therefore, in this study, leaf samples were collected from trunking (normal) and non-trunking sago palms planted on peat soil for total RNA extraction, followed by next-generation sequencing using the BGISEQ-500 platform. The raw reads were cleaned, and de novo assembled using TRINITY software package. A total of 40.11 Gb bases were sequenced from the sago palm leaf samples. The assembled sequence produced 102,447 unigenes, with N50 score 1809 bp and GC ratio of 44.34%. The alignment of unigenes with seven functional databases (NR, NT, GO, KOG, KEGG, SwissProt and InterPro) resulted in the annotation of 65,523 (63.96%) unigenes. Functional annotation results in the detection of 46,335 coding DNA sequences by Transdecoder. A total of 30,039 simple-sequence repeats distributed on 21,676 unigenes were detected using Primer3 software, and 2355 transcription factor coding unigenes were predicted using getorf and hmmseach software. This work is registered under NCBI BioProject PRJNA781491. The raw RNA sequencing data are available in Sequence Read Archive (SRA) database with accession numbers SRX13165895, SRX13165896, SRX13165897, SRX13165898, SRX13165899, and SRX13165900. Gene expression and annotation information are accessible in public functional genomics data repository Gene Expression Omnibus (GEO) with accession number GSE189085.